Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
45^10*5^20/75^15
=5^10*9^10*5^20/(5^2)^15
=5^10*5^20*9^10/5^30
=9^10
(0.8)^5/(0.4)^6
=(0.4)^5*2^5/(0.4)^6
=2^5/(0.4)
=32/(0.4)
=80
2^15*9^4/6^6*8^3
=2^15*(3^2)^4/2^6*3^6*(2^3)^3
=2^15*3^8/2^6*3^6*2^9
=3^2
=9
a) \(\frac{75^3.3^7}{81^4.5^6}=\frac{5^3.3^3.5^3.3^7}{\left(3^4\right)^4.5^6}=\frac{5^6.3^3.3^7}{3^{16}.5^6}=\frac{3^{10}}{3^{16}}=\frac{1}{3^6}=\frac{1}{729}\)
b) \(\frac{6^6.4^2}{3^{12}.2^8}=\frac{2^6.3^6.\left(2^2\right)^2}{3^{12}.2^8}=\frac{2^6.3^6.2^4}{3^{12}.2^8}=\frac{2^{10}.3^6}{3^{12}.2^8}=\frac{2^2.1}{3^6}=\frac{4}{729}\)
c) \(\frac{34^5.2^5}{2^{14}.17^5}=\frac{2^5.17^5.2^5}{2^{14}.17^5}=\frac{2^{10}}{2^{14}}=\frac{1}{2^4}=\frac{1}{16}\)
\(\dfrac{2^7\cdot9^3}{6^5\cdot8^2}=\dfrac{2^7\cdot3^6}{3^5\cdot2^5\cdot2^6}=\dfrac{3}{2^3}=\dfrac{3}{8}\)
a, (-0,2)2 \(\times\) 5 - \(\dfrac{2^{13}\times27^3}{4^6\times9^5}\)
= 0,04 \(\times\) 5 - \(\dfrac{2^{13}\times3^9}{2^{12}\times3^{10}}\)
= 0,2 - \(\dfrac{2}{3}\)
= \(\dfrac{2}{10}\) - \(\dfrac{2}{3}\)
= - \(\dfrac{7}{15}\)
b, \(\dfrac{5^6+2^2.25^3+2^3.125^2}{26.5^6}\)
= \(\dfrac{5^6+4.5^6+8.5^6}{26.5^6}\)
= \(\dfrac{5^6.\left(1+4+8\right)}{26.5^6}\)
= \(\dfrac{1}{2}\)
a, (-0,2)2 ×× 5 - 213×27346×9546×95213×273
= 0,04 ×× 5 - 213×39212×310212×310213×39
= 0,2 - 2332
= 210102 - 2332
= - 715157
b, 56+22.253+23.125226.5626.5656+22.253+23.1252
= 56+4.56+8.5626.5626.5656+4.56+8.56
= 56.(1+4+8)26.5626.5656.(1+4+8)
= 1221
3.
a) \(\left(x-1\right)^3=125\)
=> \(\left(x-1\right)^3=5^3\)
=> \(x-1=5\)
=> \(x=5+1\)
=> \(x=6\)
Vậy \(x=6.\)
b) \(2^{x+2}-2^x=96\)
=> \(2^x.\left(2^2-1\right)=96\)
=> \(2^x.3=96\)
=> \(2^x=96:3\)
=> \(2^x=32\)
=> \(2^x=2^5\)
=> \(x=5\)
Vậy \(x=5.\)
c) \(\left(2x+1\right)^3=343\)
=> \(\left(2x+1\right)^3=7^3\)
=> \(2x+1=7\)
=> \(2x=7-1\)
=> \(2x=6\)
=> \(x=6:2\)
=> \(x=3\)
Vậy \(x=3.\)
Chúc bạn học tốt!
a) \(\frac{7^3.5^8}{49.25^4}=\frac{7^3.5^8}{7^2.\left(5^2\right)^4}=7.\frac{5^8}{5^8}=7\)
b) \(\frac{3^9.25.5^3}{15.625.3^8}=\frac{3.3^8.5^2.5^3}{3.5.5^4.3^8}=\frac{5^5}{5^5}=1\)
c) Đề hơi sai roi bạn oi
d) \(\left(\frac{2}{5}-\frac{1}{2}\right)^2+\left(\frac{1}{2}+\frac{3}{5}\right)^2=\left(\frac{-1}{10}\right)^2+\left(\frac{11}{10}\right)^2=\frac{1}{100}+\frac{121}{100}=\frac{61}{50}\)
\(\dfrac{\left(0,04\right)^5}{\left(0,2\right)^6}=\dfrac{\left(\dfrac{1}{25}\right)^5}{\left(\dfrac{1}{5}\right)^6}=\dfrac{\left(\left(\dfrac{1}{5}\right)^2\right)^5}{\left(\dfrac{1}{5}\right)^6}=\dfrac{\left(\dfrac{1}{5}\right)^{10}}{\left(\dfrac{1}{5}\right)^6}=\left(\dfrac{1}{5}\right)^4=\dfrac{1}{625}\)
\(\dfrac{2^7.9^3}{8^2.2^5.3^5}=\dfrac{2^7.\left(3^2\right)^3}{\left(2^3\right)^2.2^5.3^5}=\dfrac{2^7.3^6}{2^6.2^5.3^5}=\dfrac{2^7.3^6}{2^{11}.3^5}=\dfrac{3}{2^4}=\dfrac{3}{16}\)
\(\dfrac{2^3.3^3.3.2^2.3^2+3^3}{-13}=\dfrac{2^3.2^2.3^3.3.3^2+3^3}{-13}=\dfrac{2^5.3^6+3^3}{-13}=\dfrac{3^3.\left(2^5.3^3+1\right)}{-13}=\dfrac{3^3.\left(864+1\right)}{-13}=\dfrac{3^3.865}{-13}=\dfrac{23355}{-13}\)